(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
Applying a historizing perspective, this text presents a critical consideration of different spacial imaginations and conceptions. It articulates cientific and aesthetic, sociocultural and antropolícall paradigms in order to reflect on the various relations between the socioeconomical and political situations in which Brazil and – with regional varients – also in other countries in Latin America found themselves involved, and the processes of spatial configurations that increasingly manifested themselves during the 21st century. In doing so, the paper critically highlights the conceptual contexts for the spatial practices on which this dossier reflects. Finally, the paper calls attention to the conspicuous absence of the great voices of Brazilian cenography in the reflexive discourse on these processes in Brasil and Latinamerica in the 21st century.